2013
DOI: 10.1001/jamaoto.2013.5444
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Swallow Function After Tongue Cancer Treatment Using Real-Time Magnetic Resonance Imaging

Abstract: IMPORTANCE Magnetic resonance imaging (MRI) has the advantage of imaging swallow function at any anatomical level without changing the position of patient, which can provide detailed information than modified barium swallow, by far the gold standard of swallow evaluation. OBJECTIVE To investigate the use of real-time MRI in the evaluation of swallow function of patients with tongue cancer. DESIGN, SETTING, AND PARTICIPANTS Real-time MRI experiments were performed on a Signa Excite HD 1.5-T scanner (GE Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…In the current study, a thickened barium solution resulted in an OTT of 2.6 ± 1.6 seconds. A lengthening of the OTT is known to occur in tongue tumor patients [32,33]. Pauloski et al reported that the OTT of thick solutions 1 month post-surgery is 2.33 seconds, which is similar to the present findings [34].…”
Section: Esophagus 7 26supporting
confidence: 89%
“…In the current study, a thickened barium solution resulted in an OTT of 2.6 ± 1.6 seconds. A lengthening of the OTT is known to occur in tongue tumor patients [32,33]. Pauloski et al reported that the OTT of thick solutions 1 month post-surgery is 2.33 seconds, which is similar to the present findings [34].…”
Section: Esophagus 7 26supporting
confidence: 89%
“…As a result, we are not able to comprehensively compare the changes in hyolingual and jaw movement preceding, during, and following swallows in humans to that in macaques. Further comparisons with human data, [64, 65, 7074] are necessary to fully understand the relevance of studies of macaque feeding for studies of mastication and swallowing disturbances in human.…”
Section: Discussionmentioning
confidence: 99%
“…2628 A few clinical studies of swallowing have been carried out using RT-MRI, for example comparisons to existing invasive modalities on dysphagia patients, 29 assessment of swallowing disorders in normal and brainstem lesion patients, 30 and evaluation of swallowing in postglossectomy patients have been demonstrated. 31 …”
mentioning
confidence: 99%
“…[26][27][28] A few clinical studies of swallowing have been carried out using RT-MRI, for example comparisons to existing invasive modalities on dysphagia patients, 29 assessment of swallowing disorders in normal and brainstem lesion patients, 30 and evaluation of swallowing in postglossectomy patients have been demonstrated. 31 RT-MRI has been utilized to analyze and compare speech in normal subjects and postglossectomy patients, where portions of the infected tongue are treated with surgical resection (with or without reconstruction), and radiation therapy. 32,33 Such analyses may provide patients and their speech therapists with useful information in managing speech posttreatment.…”
mentioning
confidence: 99%